Punishment and rehabilitation - Murphy, Jeffrie G. (Basic problems in philosophy series, 1973)
California District Court of Appeals. People v. Levy.--Benn, S. I. Punishment.--Kant, I. The right to punish.--Morris, H. Persons and punishment.--Bentham, J. Punishment and utility.--Rawls, J. Punishment as a practice.--Marx, K. Capital punishment.--Packer, H. L. Two models of the criminal process.--Karpman, B. Criminal psychodynamics.--Menninger, K. Therapy, not punishment.--Skinner, B. F. Punishment.--Wootton, B. A preventive system of criminal law.--Allen, F. A. Criminal justice, legal values, and the rehabilitative ideal.--Szasz, T. S. The myth of mental illness.--Murphy, J. G. Criminal punishment and psychiatric fallacies.--Murphy, J. G. Preventive detention and psychiatry.--Feinberg, J. Crime, clutchability, and individuated treatment.--Murphy, J. G. Appendix on psychosurgery.--Bibliography (p. 237-240)